+0

# Help. ​

-1
50
1
+1159

Help.

NotSoSmart  Nov 17, 2017
Sort:

#1
+1

Solve for x:
2 x^2 - 3 x + 2 = 0

Divide both sides by 2:
x^2 - (3 x)/2 + 1 = 0

Subtract 1 from both sides:
x^2 - (3 x)/2 = -1

x^2 - (3 x)/2 + 9/16 = -7/16

Write the left hand side as a square:
(x - 3/4)^2 = -7/16

Take the square root of both sides:
x - 3/4 = (i sqrt(7))/4 or x - 3/4 = 1/4 (-i) sqrt(7)

x = 3/4 + (i sqrt(7))/4 or x - 3/4 = 1/4 (-i) sqrt(7)

x = 3/4 + (i sqrt(7))/4        or           x= 3/4 - (i sqrt(7))/4

Solve for x:
x^2 - 4 x - 5 = 0

The left hand side factors into a product with two terms:
(x - 5) (x + 1) = 0

Split into two equations:
x - 5 = 0 or x + 1 = 0

x = 5 or x + 1 = 0

Subtract 1 from both sides:
x = 5                or                x = -1

Guest Nov 17, 2017
edited by Guest  Nov 17, 2017

### 10 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details